The main provisions of obtaining coloring systems for transparent finishing of products made of softwood - Chizhova M. A. (Interactive science, 2019)
the article presents the main provisions of obtaining stable water-dispersion coloring systems for coniferous wood. The paint technology uses polymer dispersions, which differ not only in the nature of the film-forming agent, but also in stabilization systems, lyophilicity, film-forming ability. For the choice of film-forming substance, for the painting of coniferous wood, it is necessary to take into account the main technical characteristics of polymer dispersions and their properties. The main directions of development of the LCP technology are the improvement of decorative and operational properties of coatings through the development of new materials and methods of their application, reducing the use of harmful substances.
Keywords: хвойная древесина; полимерные системы; устойчивые дисперсии; coniferous wood; polymeric systems; stable dispersion